Barrier Effects of the Kuroshio Current on the East Asian Northerly Monsoon: A Sensitivity Analysis. Issue 1 (December 2018) - Pan, Jiayi; Feng, Xue; Lai, Wenfeng; Devlin, Adam; Lin, Hui
Abstract Through the use of satellite scatterometer data, it is observed that the East Asian northerly monsoonal winds decrease drastically when crossing the Kuroshio Current. In a section across the Kuroshio Current region, as revealed by reanalysis data, it is suggested that the upward velocity has a two-cell structure extending to the 500 hPa height, and a strong atmospheric convergence is present below the 900 hPa level. The reanalysis data also show that the northerly wind speed decreases significantly when crossing the Kuroshio Current region below 850 hPa height. A sensitivity analysis is implemented using the Weather Research and Forecasting (WRF) model, showing that the atmospheric convergence and the northerly wind drop are enhanced as the Kuroshio region surface temperature increases. This indicates that the Kuroshio Current can act as a barrier to the East Asian northerly monsoonal winds in winter.